A Study on the Influence of Plasma Nitriding Technology Parameters on the Working Surface Deformation of Hypoid Gears - Le, H. K. (Engineering, Technology & Applied Science Research, 2022)
This paper presents the results of the research on the influence of plasma nitriding technology parameters on the working surface deformation of hypoid gears. Blue light technology with non-contact measuring devices is used to determine the working surface deformation of hypoid gears after plasma nitriding. The study has determined a regression equation showing the influence of plasma nitriding technology parameters on the deformation of the working surface of the hypoid gear. The minimum deformation optimization value at the planning area is 0.0071746 at permeation temperature TL=4.89oC, permeation time h=510h, and gas flow 1 G1=6.02L/h.